Non-structural proteins of bovine viral diarrhea virus - Chi, Shanshan; Chen, Si; Jia, Weijuan; He, Yunjiang; Ren, Linzhu; Wang, Xueli (Virus genes, 2022)
Bovine viral diarrhea virus (BVDV) belongs to the family Flaviviridae genus pestivirus. The viral genome is a single-stranded, positive-sense RNA that encodes four structural proteins (i.e., C, Erns, E1, and E2) and eight non-structural proteins (NSPs) (i.e., Npro, p7, NS2, NS3, NS4A, NS4B, NS5A, and NS5B). Cattle infected with BVDV exhibit a number of different clinical signs including diarrhea, abortion, and other reproductive disorders which have a serious impact on the cattle industry worldwide. Research on BVDV mainly focuses on its structural protein, however, progress in understanding the functions of the NSPs of BVDV has also been made in recent decades. The knowledge gained on the BVDV non-structural proteins is helpful to more fully understand the viral replication process and the molecular mechanism of viral persistent infection. This review focuses on the functions of BVDV NSPs and provides references for the identification of BVDV, the diagnosis and prevention of Bovine viral diarrhea mucosal disease (BVD-MD), and the development of vaccines.